ANTECEDENT DARI SOCIAL MEDIA PRODUK APPLE PADA MAHASISWA UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA (UMSU) - Nora Anisa Br Sinulingga (Jurnal Mantik Penusa, 2016)
The background on this research is to analyze the importance of Antecedent of Social MediaProducts Apple In UMSU Student. The purpose of this study was to determine the effect of self identification of the social identification, self identification of the brand community, social identificationon brand community, brand community on behavioral loyalty, and behavioral loyaty on social media. The sample of this research is 150 respondents who use Apple products existingin the environment UMSU.The research method used in this research is quantitative research method using primary data of questionnaire. The data was analyzed by using Structural Equation Modelling (SEM). The measurement scale of this study is using Likert scale method. The results of this study indicate that self-identification has a positive influence on social identification, self-identification has no influence on brand community, social identification has a positive influence on brand community, brand community has a positive influence on behavioral loyalty, brand community has no influence on social media, behavioral loyaltyhas a positive influence on social media.